Intralesional corticosteroid injection as a conservative treatment for central giant cell granuloma: a review of the literature - Villarreal Arizpe, Karen Lissette (2021)
Central giant cell granuloma (CGCG) is a benign intraosseous lesion of the jaws. Traditionally, surgery is the most used treatment for this type of pathology, however, in recent years the use of intralesional corticosteroids injections has been proposed as a conservative alternative. The aim of this study is to carry out a bibliographic review of the cases treated with corticosteroids. The author used PubMed and Google Scholar platforms were used to search for articles published between 1994 and 2020, related to CGCG and its treatment with corticosteroids. The results of this research were 28 articles and one abstract were found with 61 patients in total; in most cases, weekly intralesional injections of triamcinolone acetonide with anesthetic were used for 6 weeks, although protocol variants were reported. Of the 61 cases, 38 had complete resolution while the other cases required additional surgical treatment. From this, it seems that the use of intralesional triamcinolone injections have a positive effect in the treatment of CGCG by allowing a complete resolution of the lesion or a decrease in its size, so that subsequent surgery is more conservative.